PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON INVESTMENT, INVESTMENT OPPORTUNITY SET DAN FIRM SIZE TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN YANG TERMASUK DALAM JAKARTA ISLAMIC INDEX SELAMA PERIODE 2012 – 2016: The Effect of Current Ratio, Debt to Equity Ratio, Return On Investment, Investment Opportunity Set, and Firm Size On Dividend Payout Ratio in Jakarta Islamic Index During 2012-2016 Period; Pengaruh Current Ratio, Debt to Equity Ratio, Return On Investment, Invesment Opport - Mutiarahim, Noery (Universitas Multimedia Nusantara, 2019)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Return On Investment, Investment Opportunity Set, and Firm Size on Dividend Payout Ratio of Companies Listed in Jakarta Islamic Index during 2012-2016 period. This research is using annual report that collected from Indonesia Stock Exchange. The analysis data method used in this research is panel data regression analysis with the Common Effect method. The result show that Current Ratio has no positive effect on Dividend Payout Ratio, Debt to Equity Ratio has negative and significant effect on Dividend Payout Ratio, Return On Investment and Investment Opportuniy Set has no significant effect on Dividend Payout Ratio, and Firm Size has positive and significant effect on Dividend Payout Ratio. Keywords: Dividend Payout Ratio, Current Ratio, Debt to Equity Ratio, Return On Investment, Investment Opportunity Set, Firm Size, Jakarta Islamic Index.